Yum! mmmm! que rico! : Americas' sproutings - Mora, Pat (Lee & Low Books Inc., 2007)
"From blueberries to vanilla, indigenous foods of the Americas are celebrated in this collection of haiku, which also includes information about each food's origins"--Provided by publisher.